PENDEKATAN HUMANISTIK DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN PEMAHAMAN SISWA - masrikan masrikan (Jurnal Penelitian Pembelajaran Fisika, 2012)
ABSTRAKThe learning of physics today is still far from what is expected in the present curriculum. The grades are very low. The student?óÔé¼Ôäós interest and creativity in physics learning are low. Student?óÔé¼Ôäós desire to learn actively and to deeper learn physics is still low. Based on the fact, it is necessary to build a learning model which can improve comprehension in the learning of physics. The background student in SMP 38 come from the middle and under economic family. The model should be easy for teachers to adopt, and also easy for the students. In the research the humanistic approach is chosen, in this case a humanistic approach which is applicable to improve students comprehension in SMP 38 Semarang.The research is aimed at implementing the humanistic approuch to improve students?óÔé¼Ôäó comprehension in the learning of physics in junior high school students. Students?óÔé¼Ôäó comprehension in learning increases to 19,80 in the before research up to 30,68 in the four cycle. Learning achievement has not reach the did wished standart yet. It shows that physics learning model using problem based can increase student?óÔé¼Ôäós comprehension. The increasing of the comprehension will improve student?óÔé¼Ôäós learning motivation. And learning achievement will be reached when there is learning habit which caused by the improvement of student?óÔé¼Ôäós motivation.Key Words : humanistic approach, comprehension, physics learning.